Operating strategy under subsidy phase-out: joint pricing and product line configuration for electric and traditional vehicle models - Hu, Min; Chen, Sidi; Wu, Weiyu; Wei, Yan (Transformations In Business & Economics, 2026)
Against the backdrop of carbon peak and carbon neutrality targets and the transformation of the automotive industry, China’s new energy vehicle (NEV) subsidies have entered a phase of gradual reduction, leading to a substantial decrease in external incentives. Traditional automobile manufacturers qualified to produce NEVs must make production decisions between NEVs and conventional internal combustion engine vehicles based on operational performance. These decisions directly influence transformation efficiency and profit stability. However, existing research conducted under the subsidy phase-out scenario has insufficient focus on actionable threshold-type production decision rules and standardized analytical frameworks for production operations and supply chain configurations. To investigate how consumer premiums for NEV performance influence the optimal mixed production and joint pricing through the demand structure after subsidy withdrawal, drawing on structural contingency theory, a joint decision-making model is constructed with profit maximization as the objective. Static equilibrium derivation and comparative static analysis were used to characterize the response of optimal decisions to key parameters, and threshold identification was performed to define critical conditions for strategy switching. Results indicate that (1) the level of consumer premium is positively correlated with the proportion of NEV production. When the premium is below a certain threshold, manufacturers produce only conventional vehicles; when it exceeds another threshold, only NEVs are produced. (2) An increase in consumer premium leads to a decrease in the total number of car buyers, which eventually stabilizes at about half of the original scale. (3) The manufacturer’s optimal profit has a U-shaped relationship with consumer premium, that is, profits decrease initially and then increase. The conclusions provide a methodological reference and policy insights for automobile manufacturers to balance profit stability and technological diffusion in the green transition.
Keywords: operational management; production and pricing; mixed production; new energy vehicles; subsidy phase-out